Assessment of emotional intelligence in medical university staff in Ardabil: Northwest of Iran - Abbasi, Vahid; Zakeri, Anahita; Amani, Firouz; Molaei, Behnam (International Journal of Advances in Medicine, 2018)
Background: Emotional intelligence is one of the most important factors for the job and social success of individuals that is necessary for effective performance of all employees working in different governmental and private sectors, medical centers, factories and others. The aim of this study was to investigate the Emotional Intelligence (EI) in Ardabil University staff. Methods: This cross-sectional descriptive study was done on 150 staff employed in Ardabil University of Medical Sciences which selected randomly. Data collected by Goleman EI questionnaire and analysed by statistical descriptive methods in SPSS.19. Results: The mean age of samples was 7.6±40.8 and 56% of samples were male. 93.3% of samples had university degree. The EI of most of employees with 68% were in moderate level. Conclusions: Conducting appropriate and effective training courses on emotional intelligence can be very effective in promoting job success, social success, and better interaction between staff and people.